Recognition of Fibrotic Infarct Density by the Pattern of Local Systolic-Diastolic Myocardial Electrical Impedance - Amorós-Figueras, Gerard; Jorge, Esther; García-Sánchez, Tomás; Bragós, Ramón; Rosell-Ferrer, Javier; Cinca, Juan (Frontiers in Physiology, 2016)
Myocardial electrical impedance is a biophysical property of the heart that is influenced by the intrinsic structural characteristics of the tissue. Therefore, the structural derangements elicited in a chronic myocardial infarction should cause specific changes in the local systolic-diastolic myocardial impedance, but this is not known. This study aimed to characterize the local changes of systolic-diastolic myocardial impedance in a healed myocardial infarction model. Six pigs were submitted to 150 min of left anterior descending coronary artery occlusion followed by reperfusion. Four weeks later, myocardial impedance spectroscopy (1-1000 kHz) was measured at different infarction sites. The electrocardiogram, left ventricular (LV) pressure, LV dP/dt, and aortic blood flow were also recorded. A total of 59 LV tissue samples were obtained and histopathological studies were performed to quantify the percentage of fibrosis. Samples were categorized as normal myocardium (<10% fibrosis), heterogeneous scar (10-50%) and dense scar (>50%). Resistivity of normal myocardium depicted phasic changes during the cardiac cycle and its amplitude markedly decreased in dense scar (18±2Ω·cm vs 10±1Ω·cm, at 41 kHz; P<0.001, respectively). The mean phasic resistivity decreased progressively from normal to heterogeneous and dense scar regions (285±10 Ω·cm, 225±25Ω·cm, and 162±6Ω·cm, at 41 kHz; P<0.001 respectively). Moreover, myocardial resistivity and phase angle correlated significantly with the degree of local fibrosis (resistivity: r=0.86 at 1 kHz, P<0.001; phase angle: r=0.84 at 41 kHz, P<0.001). Myocardial infarcted regions with greater fibrotic content show lower mean impedance values and more depressed systolic-diastolic dynamic impedance changes.